Building Buddhist Mental Strength According to the Noble Truth 4 - Supho, Noppakao (Journal of Mahapajapati Buddhist Review, 2024)
The academic paper title Building Buddhist Mental Strength According to the Noble Truth 4 is a study of guidelines for creating mental intensity by applying to the Noble Truth 4 principle, finding that mental strength is the ability of a person to face stress and return to normal more quickly than the general public. Persistence of a state of strength is the cultivation of a person's ability to develop immunity from childhood to adulthood. The factors that support strength stem from social environment, which is to promote freedom in positive behaviors, and the basis for strengthening the Buddhist mind is to understand the Noble Truths 4. Knowing the Problem of Suffering Knowing the Source of Suffering Knowing the ways to eliminate suffering and having guidelines for how to get out of suffering is knowledge and understanding that effectively builds a person's mental strength.